Preparation and Characterization of KIT-6 / Polysulfone Mixed Matrix Membrane - Jayabalan, Jayakumaresh (Universiti Teknologi PETRONAS, 2016)
Mixed matrix membrane (MMM) is a new class of layer materials that offers the huge potential in propelling the present membrane based separation innovation. These separation membranes have been generally produced by fusing inorganic fillers such as mesoporous silica into a polymer matrix. The current project was focused on the preparation and characterization of a novel KIT-6/Polysulfone mixed matrix membranes. KIT-6 mesoporous silica which acts as the inorganic filler were synthesized using hydrothermal treatment at 100°C (oven) for 24 hours prior to the preparation of mixed matrix membranes. The synthesized KIT-6 silica were incorporated, with different amount of loading (5%, 10%, 15% & 20%) into polysulfone membrane solution in order to prepare the KIT-6/Polysulfone mixed matrix membranes.